"Blueprinting" and climate change: Regional governance and civic participation in land use and transportation planning. (December 2015) - Niemeier, Deb; Grattet, Ryken; Beamish, Thomas
This study investigates the development and performance of an innovative approach to the management of transportation, land use, air quality, housing, and a variety of other regional development issues, called "blueprinting." Blueprinting refers to a process that brings together planning experts, local political leaders, and ordinary citizens; arms them with current planning ideas about "smart growth" and data visualization tools, to develop long-range regional development plans. As such, blueprinting represents a recent manifestation of regionalist approaches to environmental policy and planning. Focusing on the Sacramento region, an early adopter of blueprint planning, we use archival data and media sources to reconstruct the development of blueprinting and then we turn to an analysis of the performance of the blueprinting approach in relation to three successive planning efforts. We find that despite the promise of blueprinting, very little progress has been made toward actually changing the regional transportation system and land use patterns. The net result of this long-term planning effort aimed at achieving sustainable transportation land use is that total CO2 emissions increase over time at historical rates. We close with a discussion of what this means for regional planning and achieving goals set by California's landmark climate change legislation.